Cardiovascular mortality in Northern Ireland during the 2008-2014 financial crisis years: who got the worst hit? (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Internationally, cardiovascular mortality and economic recessions showed an established relationship. Northern Ireland was badly affected by the global financial crisis in 2008-2014 but little is known in terms of how cardiovascular mortality was affected.Objective: The aim of the present study was to investigate the potential impact of the 2008 economic crisis on the annual cerebrovascular accidents CVA and ischaemic heart disease IHD related mortality in Northern Ireland.Method: Mortality data were extracted from Northern Ireland Statistics and Research Agency database. We utilized generalized linear regression Poisson modelling to estimate the impact of economic crisis on the IHD and CVA mortality.Results: We found a significant increase of IHD-deaths during the financial crisis years in males over the age of 65 (β = 49.466, p value = 0.003) and females over the age of 65 (β = 57.721, p value = 0.001). However, CVA-mortality in the post crisis years rose significantly for females who were 65 years or older (β = 56.010, p value = 0.005) but not for males. The rest of the age groups were not significantly affected in terms of either CVA or IHD mortality.Conclusion: For the total population the only age category with significant increase in both IHD and CVA mortality in the post-2008 era was the over 65 (p values < 0.001 and = 0.012, respectively)Declaration of interest: None.Keywords: IHD, CVA, Northern Ireland, economic recession, working-age, socio-economic changes
Keywords: IHD; CVA; Northern Ireland; economic recession; working-age; socio-economic changes